The Challenges and Opportunities of Artificial Intelligence for Entrepreneurs. Case Study of the Rabat-Salé-Kénitra Region - ARABI, Hamza EL; YAHYAOUI, Nissrine (Theoretical and Practical Research in Economic Fields; Vol 16 No 1 (2025): TPREF Volume XVI, Issue 1(33), Spring 2025, 2025)
In today’s rapidly evolving work environment, artificial intelligence (AI) is becoming a key driver of innovation and efficiency for entrepreneurs. However, with this technological progress come significant regulatory challenges that need to be addressed. This article examines how entrepreneurs can navigate these regulatory requirements while harnessing the potential of AI. The study was conducted with a sample of 50 entrepreneurs from the Rabat-Salé-Kénitra region. Data was gathered through a self-administered questionnaire, and hypotheses were tested using a structural equation model. The findings confirm that both the opportunities presented by AI and the regulatory challenges it brings have a strong, positive impact on its implementation. On the other hand, the lack of technological skills was found to have a negative but insignificant effect on the adoption of AI .